Evaluation of upper extremity function of displaced diaphyseal humeral fractures in children treated by elastic stable intramedullary nailing: preliminary results. Issue 5 (September 2016) - Canavese, Federico; Marengo, Lorenza; Samba, Antoine; Rousset, Marie; Mansour, Mounira; Andreacchio, Antonio; Dimeglio, Alain
Abstract : The aim of this study was to retrospectively evaluate the outcome of displaced humeral shaft fractures in children and adolescents treated by elastic stable intramedullary nailing (ESIN) and to evaluate upper extremity function using the Quick-DASH questionnaire. Correction was maintained over time in 14 of 16 patients. All patients were pain free at last follow-up. Shoulder and elbow ranges of motion were comparable with the noninjured side. The mean Quick-DASH score was 1. This study reports good functional outcomes in children with displaced humeral shaft fractures surgically treated with ESIN, even in the presence of residual deformity. ESIN enables stable reduction, good rotational control, and good functional outcome.